Banana Chip Making Machine With 2in1 Integrated System (Slicing And Frying) Equipped With Thermocontrol - Raniya Nur Ningsih; Hima Nurwidya Timur; Bagus Dwi Pratama; Sha’id Khana’Fi; Roby Ferdian; Agung Prijo Budijono (Journal of International Conference Proceedings (JICP), 2018)
The purpose This research is to create a prototype of Banana Chip Making Machine with 2in1 integrated system (slicing and frying) with thermocontrol, so that oil temperature during frying time is more awake and gas efficient. Methodology This study was conducted by designing Banana Chip Making Machine with 2in1 integrated system (slicing and frying) equipped with thermocontrol, where the slicing process is done by using a moving knife with eccentric system. Then the sliced banana will go straight into the frying pan with a controlled cooking temperature to produce a banana chip with a better maturity level. Result, this research resulted in a prototype of Banana Chip Machine making machine with 2in1 integrated system (slicing and frying), after testing machine performance, it was found that this machine has a capacity of 4 kg / hr where, 20 minutes for incision and 40 minutes for frying with the frying temperature reaching 250 degrees Celsius. The findings, This study found the design and prototype of Banana Chip Machine Maker with 2in1 integrated system (slicing and frying), where the machine produces better banana maturity. Keywords: slicing machine, banana, thermocontrol, frying pan